2004
DOI: 10.1109/tnn.2003.820621
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Classification Algorithms for Underwater Target Discrimination

Abstract: Abstract-Classification of underwater targets from the acoustic backscattered signals is considered here. Several different classification algorithms are tested and benchmarked not only for their performance but also to gain insight to the properties of the feature space. Results on a wideband 80-kHz acoustic backscattered data set collected for six different objects are presented in terms of the receiver operating characteristic (ROC) and robustness of the classifiers wrt reverberation.Index Terms-K-nearest n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The returning echo owns important frequency features information reflecting the target strength and the key point of underwater mine shell discrimination is robust echo features extraction process [10,14]. TF analyses, such as Wigner-Ville distribution, STFT, all produce poor results in impulse noise environment [7].…”
Section: Feature Extraction and Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The returning echo owns important frequency features information reflecting the target strength and the key point of underwater mine shell discrimination is robust echo features extraction process [10,14]. TF analyses, such as Wigner-Ville distribution, STFT, all produce poor results in impulse noise environment [7].…”
Section: Feature Extraction and Reductionmentioning
confidence: 99%
“…The canonical correlations are selected as features for classifying mine-like from non-minelike objects [17]. The authors of [14,19] demonstrated that the classification accuracy can be achieved largely when the backscattered signals' feature can be fused by some linear or nonlinear fusion schemes. Several classification algorithms of underwater targets from the acoustic backscattered signals are compared.…”
Section: Introductionmentioning
confidence: 99%
“…SVM provides a uniform framework to solve learning problem of few samples [5] . SVM classifier overcomes over-learning and local optimal value in NN method.…”
Section: Classifiersmentioning
confidence: 99%
“…The analysis of the acoustic backscattered signals of MMB and related substrates has been studied with a variety of different approaches [6][7][8][9]. One of them [9] has been the target for improvement in a work using GP [10], where GP was able to provide an improved discrimination between the different seafloor habitats.…”
Section: Introductionmentioning
confidence: 99%